Kapelusz kontra fez – o roli nakryć głowy w europeizacji Turcji - Szkudlarek, Magdalena (Wydawnictwo Naukowe WNPiD UAM w Poznaniu, 2014)
The aim of this publication is to depart from traditional perspectives and research methods in international relations and to take an attempt to analyze the process of modernization of Turkey through the prism of Objects – fez, hat and hijab. The starting point for the deliberations is Bruno Latour’s Object-oriented ontology which’s essence is statement that dichotomy between these what belong to social world and those what is material is completely unfounded. The Objects are indeed the ground and support for fragile relations and processes and create a so-called nonhuman factor, which is subject of interest of posthuman perspective. The author, using Latour’s theory as a theoretical basis, analyzes the role of headgears which evolved from common daily use things into vehcile of state- and nation-building processes.
Hat versus fez – on the role of headgear in the Europeanisation of Turkey